2004
DOI: 10.1143/jjap.43.4949
|View full text |Cite
|
Sign up to set email alerts
|

Shift Selectivity and Hologram Playback Margin Dependence on the Average Speckle Size of a Randomly Phase Encoded Reference Beam

Abstract: Several important hologram reconstruction parameters of shift multiplexing with a randomly phase encoded reference beam were investigated as functions of the reference beam average speckle size at the medium. Those are shift selectivity, reference beam defocus margin, and medium tilt margin. It was confirmed that these parameters are linearly dependent on the average speckle size in certain directions. The exception was the in-track direction medium tilt margin which is dominated by the Bragg matching conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…It has been reported that the average speckle size is much longer in the longitudinal direction than in the transversal direction, 8) which corresponds also well to our simulation results.…”
Section: Input Intensity Output Intensitysupporting
confidence: 92%
See 1 more Smart Citation
“…It has been reported that the average speckle size is much longer in the longitudinal direction than in the transversal direction, 8) which corresponds also well to our simulation results.…”
Section: Input Intensity Output Intensitysupporting
confidence: 92%
“…In order to validate our simulation of the media shift, we compared the simulation result with the speckle theory. It has been reported that in hologram recording, the medium shift selectivity and the hologram playback margin are comparable to the average speckle size, 7,8) Áx as defined:…”
Section: Tolerances Of the Collinear Optical Systemmentioning
confidence: 99%
“…Accordingly, the shift selectivity along this direction is also alleviated. 1,10) By combining the spatial multiplexing of the regions of the speckle-multiplexed holograms along this direction, storage capacity will be further increased with sufficient repositioning tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…This method enables us to relax the shift selectivity in a shift direction of holographic medium. We also notice that the hologram which is recorded with the speckled reference beam intrinsically has the relaxed shift selectivity along the propagation direction of the reference beam [1,5]. The hologram can be easily multiplexed and read out spatially along the "controlled" and the "intrinsically relaxed" directions by utilization of these relaxed shift selectivities.…”
Section: Introductionmentioning
confidence: 89%